TREATMENT FOR HEPATORENAL SYNDROME IN PEOPLE WITH DECOMPENSATED LIVER CIRRHOSIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Hepatorenal syndrome is defined as renal failure in people with cirrhosis in the absence of other causes. In addition to supportive treatment such as albumin to restore fluid balance, the other potential treatments include systemic vasoconstrictor drugs (such as vasopressin analogues or noradrenaline), renal vasodilator drugs (such as dopamine), transjugular intrahepatic portosystemic shunt (TIPS), and liver support with molecular adsorbent recirculating system (MARS). There is uncertainty over the best treatment regimen for hepatorenal syndrome. Spontaneous bacterial peritonitis occurred in 5.9% of patients. The most common cause of AKI was pre-renal. Hepatorenal syndrome was identified in 9.8% of patient encounters. Predictors of HRS were history of ascites, serum creatinine >2.5 mg/dL, albumin 2 mg/dL and spontaneous bacterial peritonitis. We demonstrate strong predictors for the development of HRS which can aid clinicians to attain an early diagnosis of HRS, leading to prompt and targeted management and improving outcomes.